2017
DOI: 10.1002/bdd.2101
|View full text |Cite
|
Sign up to set email alerts
|

Acetylshikonin is a novel non‐selective cytochrome P450 inhibitor

Abstract: Acetylshikonin is a biologically active compound with anti-cancer and anti-inflammatory activity, which is isolated from the roots of Lithospermum erythrorhizoma. An inhibitory effect of acetylshikonin against CYP2J2 activity was discovered recently. Based on this result, this study was expanded to evaluate the inhibitory effects of acetylshikonin against nine different cytochrome P450 (P450) isoforms in human liver microsomes (HLMs) using substrate cocktails incubation assay. Acetylshikonin showed a strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Shon et al. ( 2017 ) reported that acetylshikonin could act as a novel non-selective cytochrome P450 inhibitor to produce significant inhibitory effects on nine cytochrome P450 isoforms (i.e., CYP 1A2, CYP 2A6, CYP 2B6, CYP 2C8, CYP 2C9, CYP 2C19, CYP 2D6, CYP 2E1, and CYP 3 A). In another study, the proliferation and migration of angiotensin II-induced cerebrovascular smooth muscle cells were inhibited by acetylshikonin through suppression of Wnt/β-catenin pathway (Li et al.…”
Section: Pharmacologymentioning
confidence: 99%
“…Shon et al. ( 2017 ) reported that acetylshikonin could act as a novel non-selective cytochrome P450 inhibitor to produce significant inhibitory effects on nine cytochrome P450 isoforms (i.e., CYP 1A2, CYP 2A6, CYP 2B6, CYP 2C8, CYP 2C9, CYP 2C19, CYP 2D6, CYP 2E1, and CYP 3 A). In another study, the proliferation and migration of angiotensin II-induced cerebrovascular smooth muscle cells were inhibited by acetylshikonin through suppression of Wnt/β-catenin pathway (Li et al.…”
Section: Pharmacologymentioning
confidence: 99%